Edukasi Keamanan Pangan Kepada Masyarakat Desa Maku - Mariyani (VINICHO MEDIA PUBLISINDO, 2023)
Food that is consumed must have good quality to meet human needs. To meet consumer demand, a food additive is needed, one of which is sodium benzoate which can function to extend the shelf life of these food ingredients. However, sodium benzoate has regulated the maximum level for consumption so that it remains safe for the body and does not cause side effects. Through community service activities, food safety counseling was conducted for the community to increase information about food additives that are allowed and how to check food products through CEK KLIK, in addition to free health checks and distribution of basic necessities to help the basic needs of people in need. This activity resulted in an increase in community understanding about food, and it is hoped that it can help the community in general and this activity can be sustainable.